Outside Front Cover: Plasma Process. Polym. 12/2022. Issue 12 (5th December 2022) - Wang, Huichao; Zhao, Tong; Wang, Xiaolong; Wang, Daohan; Zhang, Yuantao
Abstract : Outside Front Cover : The OH radicals in cold atmospheric plasma cause irreversible damage to the configuration of succinate dehydrogenase. Hydrogen abstraction reaction is the basic way of OH oxidation damage to SDH. Cysteine, lysine and tyrosine were the top three amino acids involved in the reaction. The utilization rate of the OH radicals decreased increasing OH concentration, while the damaging effect was weakened. Further details can be found in the article by Huichao Wang, Tong Zhao, Xiaolong Wang, Daohan Wang, and Yuantao Zhang (e2200083 )